mTOR inhibitor reverses autistic-like social deficit behaviours in adult rats with both Tsc2 haploinsufficiency and developmental status epilepticus - Schneider, Miriam (European archives of psychiatry and clinical neuroscience, 2017)
Epilepsy is a major risk factor for autism spectrum disorder (ASD) and complicates clinical manifestations and management of ASD significantly. Tuberous sclerosis complex (TSC), caused by TSC1 or TSC2 mutations, is one of the medical conditions most commonly associated with ASD and has become an important model to examine molecular pathways associated with ASD. Previous research showed reversal of autism-like social deficits in Tsc1 +/− and Tsc2 +/− mouse models by mammalian target of rapamycin (mTOR) inhibitors. However, at least 70 % of individuals with TSC also have epilepsy, known to complicate the severity and treatment responsiveness of the behavioural phenotype. No previous study has examined the impact of seizures on neurocognitive reversal by mTOR inhibitors. Adult Tsc2 +/− (Eker)-rats express social deficits similar to Tsc2 +/− mice, with additive social deficits from developmental status epilepticus (DSE). DSE was induced by intraperitoneal injection with kainic acid at post-natal days P7 and P14 (n = 12). The experimental group that modelled TSC pathology carried the Tsc2 +/− (Eker)-mutation and was challenged with DSE. The wild-type controls had not received DSE (n = 10). Four-month-old animals were analysed for social behaviour (T1), then treated three times during 1 week with 1 mg/kg everolimus and finally retested in the post-treatment behavioural analysis (T2). In the experimental group, both social interaction and social cognition were impaired at T1. After treatment at T2, behaviour in the experimental group was indistinguishable from controls. The mTOR inhibitor, everolimus, reversed social deficit behaviours in the Tsc2 haploinsufficiency plus DSE animal model to control levels.
Gesehen am 12.07.2018
Published online: 4 June 2016